The Impeccable Zapu and ANC Alliance in Retrospect: The 1967 Wankie and 1968 Sipolilo Campaigns - Dumiso Dabengwa (The Thinker)
For ZPRA the battle of Wankie was understandably the watershed in the history of Zimbabwe and South Africa's armed liberation struggles. The Luthuli detachment’s indomitable fighters proved the lie of the invincibility of the Rhodesian and South African racist and apartheid regimes.